Poor Specificity of Screening Tests for the Detection of Staphylococcus aureus with Reduced Susceptibility to Vancomycin - Friedman, Deborah N; Midolo, Peter D; Kotsanas, Despina; Korman, Tony M (International Journal of Infection Control, 2009)
Between July 2001 and December 2003, Staphylococcus aureus with reduced susceptibility to vancomycin was detected by screening tests in 22 isolates at our institution. This report is a cautionary note about the results of screening tests without confirmatory testing for the laboratory identification of vancomycin-intermediate S. aureus.